Information Quality, Performance Measurement, and Security Demand in Rational Expectations Economies. - Noe, Thomas H; Ramamurtie, Buddhavarapu Sailesh (Journal of Finance, 1995)
The relationship between asset demand and information quality in rational expectations economies is analyzed. First the authors derive a number of new summary descriptive statistics that measure four basic characteristics of investment style: asset selection, market timing, aggressiveness, and specialization. Then they relate these statistics to the divergence between a given investor's information structure and the market average information structure. Finally, the authors demonstrate that informational differentials can be identified and consistently estimated, using ordinary least squares, from the time-series of observed asset demand.